Chemical oxygen demand and nitrogen transformation in a large pilot-scale plant with a combined submerged anaerobic membrane bioreactor and one-stage partial nitritation-anammox for treating mainstream wastewater at 25 °C. (December 2021) - Rong, Chao; Luo, Zibin; Wang, Tianjie; Guo, Yan; Kong, Zhe; Wu, Jiang; Ji, Jiayuan; Qin, Yu; Hanaoka, Taira; Sakemi, Shinichi; Ito, Masami; Kobayashi, Shigeki; et al.
Highlights: A pilot-scale SAnMBR-PN/A plant was successfully applied for real municipal wastewater treatment. The overall COD and total nitrogen removal efficiencies were 95.1% and 81.7%, respectively. The biogas yield rate was 0.09 NL L −1 of treated wastewater with a methane content of 80%. Denitrification occurred in PN/A unit, enhancing overall COD and nitrogen removal. Abstract: A novel municipal wastewater treatment process towards energy neutrality and reduced carbon emissions was established by combining a submerged anaerobic membrane bioreactor (SAnMBR) with a one-stage partial nitritation-anammox (PN/A), and was demonstrated at pilot-scale at 25 °C. The overall COD and BOD5 removal efficiencies were 95.1% and 96.4%, respectively, with 20.3 mg L −1 COD and 5.2 mg L −1 BOD5 remaining in the final effluent. The total nitrogen (TN) removal efficiency was 81.7%, resulting 7.3 mg L −1 TN was discharged from the system. The biogas yield was 0.222 NL g −1 COD removed with a methane content range of 78–81%. Approximately 90% of influent COD was removed in the SAnMBR, and 70% of influent nitrogen was removed in the PN/A. The denitrification which occurred in the PN/A enhanced overall COD and nitrogen removal. The successful operation of this pilot-scale plant indicates the SAnMBR-PN/A process is suitable for treating real municipal wastewater.